10-year cardiovascular disease risk and its predictors: a comparison between healthcare workers and the general public in Qatar - Sami Abdeen (14779537) (2025)
Background The scientific literature presents conflicting findings on whether health care workers (HCWs) have better, or worse, cardiovascular health compared to the general population. The study aimed to compare the 10-year atherosclerotic cardiovascular disease (ASCVD) risk between the general public and HCWs in Qatar. Methods An analytical cross-sectional study was conducted, involving two study groups: the general public and HCWs. Data collection included primary data collected through telephone interviews, as well as secondary data extracted from electronic health records. Combining these data, 10-year ASCVD risk was calculated using the American College of Cardiology/American Heart Association (ACC/AHA) risk calculator and compared between the two groups. Additionally, multivariable logistic regression analyses were performed to identify factors associated with higher risk among each group. Results A total of 644 participants were included in this study, with 316 from the general public and 328 HCWs. The mean age of the participants was approximately 42 years, with females comprising 52.2% of the total sample. The general public had a significantly higher mean 10-year ASCVD risk than HCWs (8.0% vs. 3.4%, p < 0.001), even after adjusting for age and gender. Lifestyle emerged as the main independent predictor for higher ASCVD risk in both groups. Additionally, living alone and being a nurse were significant independent predictors of higher risk among HCWs. Conclusions The study found that HCWs have significantly lower ASCVD risk than the general public, mainly due to their healthier lifestyle habits. These findings can help guide policymakers in developing national and community-based strategies to promote healthy lifestyles among the general public in Qatar. Other Information Published in: BMC Public Health License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s12889-025-23999-0